2018
DOI: 10.26717/bjstr.2018.09.001831
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Composition and Antioxidant Properties of Clove Products

Abstract: The volatile chemical composition and antioxidant properties of whole and ground clove buds have been revisited together with those from essential oils. The major bioactive compounds showed to be eugenol, eugenyl acetate and β-caryophyllene; their different quantitative contribution justifies the unequal aroma and antioxidant properties of clove products. Eugenol was identified as the most abundant chemical from whole clove buds and essential oils, while β-caryophyllene is the dominant compound of ground clove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Haro-González et al (2021) reported that the main constituents of clove are eugenol, eugenol acetate, and caryophyllene. In addition, clove is one of the most abundant plant sources of phenolic compounds such as eugenol, eugenol acetate, and β-caryophyllene (Uddin et al, 2017;Gaspar et al, 2018). The essential oil of clove has been reported to possess many positive benefits through its antioxidant, antimicrobial, anticancer, and wound-healing activities (Bachiega et al, 2012;Percival et al, 2012;Cortés-Rojas et al, 2014;Zari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Haro-González et al (2021) reported that the main constituents of clove are eugenol, eugenol acetate, and caryophyllene. In addition, clove is one of the most abundant plant sources of phenolic compounds such as eugenol, eugenol acetate, and β-caryophyllene (Uddin et al, 2017;Gaspar et al, 2018). The essential oil of clove has been reported to possess many positive benefits through its antioxidant, antimicrobial, anticancer, and wound-healing activities (Bachiega et al, 2012;Percival et al, 2012;Cortés-Rojas et al, 2014;Zari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the 4 -hydroxyl group of eugenol specifically interacts with the lysine residue of the protein [33], which might prevent/delay fibrillization. Eugenol can easily cross the BBB and is c apable of reducing the hippocampal Aβ plaques in animal models [59,60]. Therefore, it is speculated that aromatic compounds in CL-EA and CL-H interfere with β sheet structure of the protein through π-stacking or hydrophobic interaction, impairing Aβ fibrillization.…”
Section: Discussionmentioning
confidence: 99%
“…The dose-dependent reduction in ROS observed in our study indicates the antioxidant nature of the extracts and compounds tested. Both eugenol and β-caryophyllene are the main components of clove extract, which are well-known for their antioxidant action at low concentrations by preventing lipid peroxidation and preserving the levels of antioxidative enzymes [58][59][60][61][62][63] via maintaining oxidative balance through the sirtuin-1 (SIRT1) pathway [62]. Antioxidant activity is increased by the presence of the methoxy group and the number of hydroxyl groups in the phenol ring [59].…”
Section: Discussionmentioning
confidence: 99%
“…Handwash made mostly of herbs shields us against numerous everyday encounters. Gaspar et al (2018) Natural substances with antibacterial qualities are frequently found in herbal handwashes and hand sanitizers. Aloe vera, neem, tea tree oil, lavender, and eucalyptus are a few typical natural constituents.…”
Section: Introductionmentioning
confidence: 99%